2008
DOI: 10.1007/s00595-007-3692-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous open-heart surgery and pectus deformity correction

Abstract: Purpose. Pectus deformities and cardiac problems sometimes require simultaneous surgery. We report our experience of performing this surgery and review the relevant literature. Methods. We performed simultaneous pectus deformity correction and open-heart surgery in six patients between 1999 and 2006. The pectus deformities were pectus carinatum in one patient and pectus excavatum in fi ve patients. The cardiac problems were coronary artery disease in one patient, an atrioseptal defect (ASD) with a ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…[3][4][5] Staged operations were formerly recommended; 3) however, single-stage operations have been reported with favorable results in recent years. [4][5][6][7] We decided to perform simultaneous AVR and PE correction using the modified Ravitch procedure 6) to avoid any postoperative cardiopulmonary complications that may result from mechanical compression due to uncorrected sternal deformities. The patient was substantially relieved of his complaint; however, the single-stage operation using the modified Ravitch procedure induced excessive bleeding and a high-volume transfusion secondary to the prolonged operation time and postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Staged operations were formerly recommended; 3) however, single-stage operations have been reported with favorable results in recent years. [4][5][6][7] We decided to perform simultaneous AVR and PE correction using the modified Ravitch procedure 6) to avoid any postoperative cardiopulmonary complications that may result from mechanical compression due to uncorrected sternal deformities. The patient was substantially relieved of his complaint; however, the single-stage operation using the modified Ravitch procedure induced excessive bleeding and a high-volume transfusion secondary to the prolonged operation time and postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Okay, et al 4) reported that a single-stage operation using the modified Ravitch procedure was performed without major complications such as excessive bleeding; the average total volume of blood loss in two patients who underwent Bentall's operation was 1095 ml, although the average cardiac operation time was 250 min. In contrast, in our case, the total volume of blood loss was 3990 ml, regardless of the shorter CPB duration of 171 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repair of both the PE and cardiac disease in a single stage is preferable to avoid postoperative difficulties that may result from cardiac compression or displacement into the left thoracic cavity. [4][5][6] Historically, modifications of the open Ravitch-type procedure have been used exclusively for simultaneous repair of the PE and cardiac disease due to the complex nature and greater severity of deformities in adult patients with Marfan syndrome. 4,6,7 Since its introduction by Nuss et al, 8 clinical results have shown the Minimally Invasive Repair PE (MIRPE) to be safe and successful in the Marfan syndrome patient.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Historically, modifications of the open Ravitch-type procedure have been used exclusively for simultaneous repair of the PE and cardiac disease due to the complex nature and greater severity of deformities in adult patients with Marfan syndrome. 4,6,7 Since its introduction by Nuss et al, 8 clinical results have shown the Minimally Invasive Repair PE (MIRPE) to be safe and successful in the Marfan syndrome patient. [8][9][10] We describe simultaneous cardiac surgery and chest wall repair in two Marfan adults using a modified MIRPE.…”
Section: Introductionmentioning
confidence: 99%